Self-perception of knowledge and adherence reflecting the effectiveness of antiretroviral therapy - Dagli-Hernandez, Carolina [UNESP]; Lucchetta, Rosa Camila [UNESP]; de Nadai, Tales Rubens; Galdurï¿½z, Josï¿½ Carlos Fernandez; Mastroianni, Patricia de Carvalho [UNESP] (Taylor & Francis, 2016)
Objectives: To evaluate which indirect method for assessing adherence best reflects highly active antiretroviral therapy (HAART) effectiveness and the factors related to adherence. Method: This descriptive, cross-sectional study was performed in 2012 at a reference center of the state of Sï¿½o Paulo. Self-report (simplified medication adherence questionnaire [SMAQ]) and drug refill parameters were compared to the viral load (clinical parameter of the effectiveness of pharmacotherapy [EP]) to evaluate the EP. The “Cuestionario para la Evaluaciï¿½n de la Adhesiï¿½n al Tratamiento Antiretroviral” (CEAT-VIH) was used to evaluate factors related to adherence and the EP and, complementarily, patient self-perception of adherence was compared to the clinical parameter of the EP. Results: Seventy-five patients were interviewed, 60 of whom were considered as adherent from the clinical parameter of the EP and ten were considered as adherent from all parameters. Patient self-perception about adherence was the instrument that best reflected the EP when compared to the standardized self-report questionnaire (SMAQ) and drug refill parameter. The level of education and the level of knowledge on HAART were positively correlated to the EP. Forgetfulness, alcohol use, and lack of knowledge about the medications were the factors most frequently reported as a cause of nonadherence. Conclusion: A new parameter of patient self-perception of adherence, which is a noninvasive, inexpensive instrument, could be applied and assessed as easily as self-report (SMAQ) during monthly drug refill, since it allows monitoring adherence through pharmaceutical assistance. Therefore, patient adherence to HAART could be evaluated using self-perception (CEAT-VIH) and the viral load test.
Keywords: Acquired immunodeficiency syndrome; Anti-HIV agents; Antiretroviral therapy; Health literacy; Highly active; Patient compliance